2019
DOI: 10.3390/cancers12010086
|View full text |Cite
|
Sign up to set email alerts
|

Conversion Surgery in Metastatic Gastric Cancer and Cancer Dormancy as a Prognostic Biomarker

Abstract: The role of conversion surgery in metastatic gastric cancer remains unclear. Cancer dormancy markers might have a role in predicting the survival in patients with conversion surgery. We identified 26 patients who went through conversion surgery, i.e., a curative-intent gastrectomy with metastasectomy after chemotherapy in initially metastatic gastric cancer. As controls, 114 potential candidates for conversion surgery who only received chemotherapy were included for the propensity score matching. Conversion su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…In addition, CACNA1D was found to be expressed on pancreatic islets and play a vital role in insulin secretion, which is involved in β-cell physiology and pathophysiology 31 , and AP1M2 expression was found to be upregulated only in pancreatic cancer 32 . Other genes, such as CCDC148 33 , SH3RF2 34 , VGLL1 35 and NET1 36 , were found to regulate different cell behaviors (such as cell proliferation and migration, cell death and cell cycle) involved in the development and progression of gastric cancer, whereas POLD3 was reported to be required for cell cycle progression and DNA synthesis and to be responsible for the high frequency of genomic duplications in human cancers 37 . No study was found on role of C4orf19 in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CACNA1D was found to be expressed on pancreatic islets and play a vital role in insulin secretion, which is involved in β-cell physiology and pathophysiology 31 , and AP1M2 expression was found to be upregulated only in pancreatic cancer 32 . Other genes, such as CCDC148 33 , SH3RF2 34 , VGLL1 35 and NET1 36 , were found to regulate different cell behaviors (such as cell proliferation and migration, cell death and cell cycle) involved in the development and progression of gastric cancer, whereas POLD3 was reported to be required for cell cycle progression and DNA synthesis and to be responsible for the high frequency of genomic duplications in human cancers 37 . No study was found on role of C4orf19 in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Cooperation of RTEF-1, as a downstream effector of the Hippo-YAP/TAZ pathway, with transcription factors is a common cellular phenomenon. RTEF-1 was reported to be regulated by PI3K/AKT/β-catenin signaling, which activated the transcription of MMP9, a key molecule that promotes gastric cancer cell proliferation and metastasis [ 23 ]. Furthermore, specific activator or inhibitor of Wnt/β-catenin signaling used in RTEF-1 overexpressed or siRNA VSMCs, respectively, has further suggested that Wnt/β-catenin signaling was involved in the anti-calcifying effect of RTEF-1.…”
Section: Discussionmentioning
confidence: 99%
“…However, a tumor suppressor role of USP9X has been documented in pancreatic, colorectal, and renal cancer. The various substrates of USP9X are responsible for its complex role [ 17 - 19 ]. More importantly, the clinical significance and the biological roles of USP9X in cholangiocarcinoma remain unexplored.…”
Section: Introductionmentioning
confidence: 99%